"It makes me feel not so alone": features of the Choose to Move physical activity intervention that reduce loneliness in older adults - Thea Franke; Joanie Sims-Gould; Lindsay Nettlefold; Callista Ottoni; Heather A. McKay (BMC, 2021)
Abstract Background Despite the well-known health benefits of physical activity (PA), older adults are the least active citizens. Older adults are also at risk for loneliness. Given that lonely individuals are at risk for accelerated loss of physical functioning and health with age, PA interventions that aim to enhance social connectedness may decrease loneliness and increase long-term PA participation. The objectives of this mixed-method study are to: (1) evaluate whether an evidence-based PA intervention (Choose to Move; CTM) influenced PA and loneliness differently among self-identified 'lonely' versus 'not lonely' older adults and (2) to describe factors within CTM components most likely to promote social connectedness/reduce loneliness. Methods CTM is a flexible, scalable, community-based health promoting physical activity intervention for older adults. Two community delivery partner organizations delivered 56 CTM programs in 26 urban locations across British Columbia. We collected survey data from participants (n = 458 at baseline) at 0 (baseline), 3 (mid-intervention) and 6 (post-intervention) months. We conducted in depth interviews with a subset of older adults to understand how CTM facilitated or impeded their PA and social connectedness. Results PA increased significantly from baseline to 3 months in lonely and not lonely participants. PA decreased significantly from 3 to 6 months in lonely participants; however, PA at 6 months remained significantly above baseline levels in both groups. Loneliness decreased significantly from baseline to 3 and 6 months in participants identifying as lonely at baseline. Factors within CTM components that promote social connectedness/reduce loneliness include: Activity coach characteristics/personality traits and approaches; opportunity to share information and experiences and learn from others; engagement with others who share similar/familiar experiences; increased opportunity for meaningful interaction; and accountability. Conclusion Health promoting interventions that focus on PA and social connectedness through group-based activities can effectively reduce social isolation and loneliness of older adults. Given the 'epidemic of loneliness' that plagues many countries currently, these kinds of interventions are timely and important. Research that further delineates mechanisms (e.g., sharing experiences vs. lectures), that modify the effect of an intervention on social connectedness outcomes for older adults engaged in community-based PA programs would be a welcome addition to the literature.